Integrating Functional Analysis in the Next-Generation Sequencing Diagnostic Pipeline of RASopathies - Gordon K. C. Leung (Nature Portfolio, 2018)
Abstract RASopathies are a group of heterogeneous conditions caused by germline mutations in RAS/MAPK signalling pathway genes. With next-generation sequencing (NGS), sequencing capacity is no longer a limitation to molecular diagnosis. Instead, the rising number of variants of unknown significance (VUSs) poses challenges to clinical interpretation and genetic counselling. We investigated the potential of an integrated pipeline combining NGS and the functional assessment of variants for the diagnosis of RASopathies. We included 63 Chinese patients with RASopathies that had previously tested negative for PTPN11 and HRAS mutations. In these patients, we performed a genetic analysis of genes associated with RASopathies using a multigene NGS panel and Sanger sequencing. For the VUSs, we evaluated evidence from genetic, bioinformatic and functional data. Twenty disease-causing mutations were identified in the 63 patients, providing a primary diagnostic yield of 31.7%. Four VUSs were identified in five patients. The functional assessment supported the pathogenicity of the RAF1 and RIT1 VUSs, while the significance of two VUSs in A2ML1 remained unclear. In summary, functional analysis improved the diagnostic yield from 31.7% to 36.5%. Although technically demanding and time-consuming, a functional genetic diagnostic analysis can ease the clinical translation of these findings to aid bedside interpretation.